EKSPANSI MNC STARBUCKS COFFEE DI ASIA (STUDI KASUS: CINA) - Ruri Rizaldi; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
China has knowing as the most fast and largest population in the world, as soon asChina known as the most large market in the world. Many MNC try to expand theirbusiness in China, many international brand, as Pierre Cardine, Mc Donald, Nestle,most of MNC in the world try to dominate in China. But the local taste, and loyaltyabout local brand is really tied in China’s life. Many other is give up over China,because of that. But, amazing thing hapen again with Starbucks, after Starbucks cometo China in 1998, coffee become trend in China. Even it’s bring many impact forChina.This research uses Comparative AdvantagesTheory related to Diamond conceptwhich has been revealed by Michael E. Porter. This research is Qualitative researchwhich is used by library observation.The result of this research prove that there’spositive impact for both house and home country from Multinational Corporation(especially in this case is Starbucks), and thats why MNC now being one of actor ininternational relation, and thats why the strategy of MNC become one of the issues ofthe international relation studies. Starbucks as one of the most succesful MNC hastheir own way in China, consider to Porter theory, that was four factor reliable on thisstrategy, that is: 1) factor condition; 2) demand condition; 3) relating and suppportingindustries; and 4) firm strategy, structure, and rivalry.Keywords: MNC in China, MNC Strategy, Multi National Corporation, Starbucks